A super hydrophobic thermal conductive insulating coating and preparation method thereof
By introducing fluorine atoms and hydrophobic groups to modify graphene and combining with fluorine-containing elastomer polymers, the problems of insufficient film forming, dispersibility and bonding strength of graphene materials are solved, and the coating effect of high thermal conductivity, insulation and ultra-hydrophobicity is achieved.
Patent Information
- Application Number
- CN202411353116.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing graphene materials have shortcomings in film forming, dispersibility and non-covalent binding strength, which limits their application in various fields.
Modified graphene is prepared by introducing fluorine atoms and combining them with hydrophobic groups, and combined with fluorine-containing elastomer polymers to form an ultrahydrophobic thermally conductive insulating coating with high thermal conductivity and insulating properties.
It achieves the high thermal conductivity and insulation characteristics of the paint, and has an ultra-hydrophobic effect, which improves the durability and dispersion of the paint, and overcomes the cumbersome conditions that traditional paints require high-temperature drying.
Smart Images

Figure ORQKL8E3UF0UCTVMRVW4XLWTXLLYPYUTJIZJWGV8
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings and relates to a super hydrophobic thermal conductive insulating coating and a preparation method thereof. Background Art
[0002] Super hydrophobic coating refers to coating a layer or layers of super hydrophobic material on the solid surface to achieve its anti-corrosion, waterproof, anti-icing, self-cleaning and other functions with a high water contact angle (>150°) and a low rolling angle (<10°). Super hydrophobic coatings show important value in daily life, industrial applications and scientific research. The low surface energy of the surface coated with super hydrophobic coatings can keep it from being contaminated for a long time and achieve good self-cleaning and stain resistance. In nature, the surface of lotus leaves not only has a layer of waxy substance that acts as a low surface energy, but also has a double-layer microstructure, which is composed of micron-scale cells and nanoscale waxy crystals on the cells. Studies have found that the formation of super hydrophobic surfaces is attributed to two factors, one is the low surface energy substance, and the other is the surface micro-nano rough structure.
[0003] Graphene has a layered crystal structure that exhibits low interlayer shear strength and high in-plane strength, so it has excellent thermal conductivity, water resistance, and chemical stability. Research has found that by introducing fluorine atoms, the original sp 2 Hybridized carbon atoms are converted to sp 3 The hybrid form forms a carbon-fluorine bond (CF) with fluorine atoms through a σ bond, while retaining the graphene-like honeycomb carbon skeleton structure. As the number of fluorine atoms introduced increases, the conjugated structure of the graphene skeleton is continuously destroyed, and eventually the conductive graphene is transformed into a fluorinated graphene insulating material with a resistance of more than 1 GΩ. Since the surface energy is even lower than that of graphene, it has deficiencies in film forming, dispersibility, and non-covalent bonding strength, which limits its application in various fields. Summary of the invention
[0004] The present invention relates to a super hydrophobic thermally conductive insulating coating and a preparation method thereof, and belongs to the technical field of coatings. The super hydrophobic thermally conductive insulating coating disclosed in the present invention comprises the following raw material components: a fluorine-containing elastomer polymer, an organic acid, a solvent, a vulcanizing agent and modified graphene. The present invention uses modified graphene as a filler, and has high thermal conductivity and insulation properties. Its surface is coated with a fluorine-containing elastomer polymer to form two layers of low surface energy substances, and the micro-nano rough structure on the surface of the modified graphene forms a super hydrophobic effect. And after the fluorine-containing elastomer polymer coated on the surface is worn off for a long time, the modified graphene in the inner layer still has a super hydrophobic effect, which improves the durability of the coating. In addition, the dispersibility of the fluorinated graphene and its compatibility with the fluorine-containing elastomer polymer are improved by introducing hydrophobic groups.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A super hydrophobic thermally conductive insulating coating comprises the following raw materials in parts by weight: 80-100 parts of a fluorine-containing elastomer polymer, 2-5 parts of an organic acid, 300-400 parts of a solvent, 2-5 parts of a vulcanizing agent and 20-40 parts of modified graphene. The modified graphene is prepared by fluorinating graphene oxide to obtain fluorinated graphene, and then introducing a hydrophobic group to obtain the modified graphene.
[0007] Furthermore, the preparation method of the modified graphene comprises the following steps:
[0008] (1) ultrasonically mixing graphene oxide with distilled water, then adding ammonium fluorotitanate and boric acid and stirring and mixing, and transferring to a reactor for heating, and then cooling and washing with distilled water, and drying in a drying oven to obtain fluorinated graphene;
[0009] (2) fluorinated graphene, 3-(trimethylsilyl)phenylboronic acid and distilled water are mixed, and then a palladium catalyst is added and heated. After cooling, the mixture is washed with distilled water and dried to obtain modified graphene.
[0010] Furthermore, in the step (1), the ratio of graphene oxide, distilled water, ammonium fluorotitanate and boric acid is 100-120 mg: 100-120 mL: 1-2 g: 1 g, wherein the graphene oxide is composed of nano-graphene oxide and micro-graphene oxide in a mass ratio of 1:1, and the stirring and mixing time is 6-9 min.
[0011] Furthermore, in the step (1), the heating temperature and time are 160-180° C. and 5-6 h respectively, the cooling refers to cooling to room temperature, and the drying temperature and time are 80-100° C. and 1-2 h respectively.
[0012] Furthermore, in the step (2), the mass ratio of the fluorinated graphene, 3-(trimethylsilyl)phenylboric acid and palladium catalyst is 5-8:2:0.1-0.2, the ratio of the fluorinated graphene to distilled water is 2g:30-40mL, the heating temperature and time are 80-120°C and 30-60min respectively, and the drying temperature and time are 80-100°C and 30min respectively.
[0013] Furthermore, the preparation method of the palladium catalyst in the step (2) is: mixing an aluminum nitrate solution with silicon dioxide to form a mixed solution, making the pH of the mixed solution 6, then calcining to obtain a solid, putting the solid into a sodium chloropalladate solution, drying, and calcining to obtain a palladium catalyst, the mass ratio of the aluminum nitrate solution to the silicon dioxide is 2:1.8, wherein the mass fraction of the aluminum nitrate solution is 10-20%, the calcination temperature is 200-300°C, the mass ratio of the solid to the sodium chloropalladate solution is 1:0.15-0.18, wherein the mass fraction of the sodium chloropalladate solution is 20-35%.
[0014] Furthermore, the fluorine-containing elastomer polymer is composed of polytrifluoropropylmethylsiloxane and polyvinylidene fluoride-hexafluoropropylene copolymer in a mass ratio of 1:1, the organic acid is acetic acid, the solvent is acetone, and the vulcanizing agent is composed of monosodium thiocyanate and hydroquinone in a mass ratio of 1:1.
[0015] Furthermore, the preparation method of the super hydrophobic thermally conductive insulating coating is: adding the modified graphene into a solvent and stirring and dispersing it, and then adding other raw material components and stirring and mixing them to obtain the super hydrophobic thermally conductive insulating coating.
[0016] Beneficial effects of the present invention:
[0017] The present invention uses modified graphene as filler, has high thermal conductivity and insulation properties, and its surface is coated with a fluorinated elastomer polymer to form two layers of low surface energy substances. The micro-nano rough structure on the surface of the modified graphene forms a super hydrophobic effect. After the fluorinated elastomer polymer coated on the surface is worn off for a long time, the modified graphene in the inner layer still has a super hydrophobic effect, which improves the durability of the coating. In addition, the hydrophobic group of 3-(trimethylsilyl)phenylboronic acid is introduced into the fluorinated graphene to improve the dispersibility and compatibility with the fluorinated elastomer polymer, further improving the super hydrophobicity.
[0018] Using monosodium thiocyanate and hydroquinone as vulcanizing agents, monosodium thiocyanate can increase the rate and efficiency of the vulcanization reaction, while hydroquinone can stabilize the vulcanization process and reduce the impact of side reactions and unstable factors. The combination of the two makes the vulcanization process both rapid and stable. The combination of the two with organic acids enables the coating to form a film quickly at a lower temperature, overcoming the cumbersome condition of drying at high temperature. DETAILED DESCRIPTION
[0019] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.
[0020] A super hydrophobic thermally conductive insulating coating comprises the following raw materials in parts by weight: 80 parts of a fluorine-containing elastomer polymer, 2 parts of an organic acid, 300 parts of a solvent, 2 parts of a vulcanizing agent and 20 parts of modified graphene. The modified graphene is prepared by fluorinating graphene oxide to obtain fluorinated graphene, and then introducing a hydrophobic group to obtain the modified graphene.
[0021] The preparation method of the modified graphene comprises the following steps:
[0022] (1) ultrasonically mixing graphene oxide with distilled water, then adding ammonium fluorotitanate and boric acid and stirring and mixing, and transferring to a reactor for heating, and then cooling and washing with distilled water, and drying in a drying oven to obtain fluorinated graphene;
[0023] (2) fluorinated graphene, 3-(trimethylsilyl)phenylboronic acid and distilled water are mixed, and then a palladium catalyst is added and heated. After cooling, the mixture is washed with distilled water and dried to obtain modified graphene.
[0024] In the step (1), the ratio of graphene oxide, distilled water, ammonium fluorotitanate and boric acid is 100 mg:100 mL:1 g:1 g, wherein the graphene oxide is composed of nano-graphene oxide and micro-graphene oxide in a mass ratio of 1:1, and the stirring and mixing time is 6 minutes.
[0025] The heating temperature and time in step (1) are 160° C. and 5 h respectively, the cooling refers to cooling to room temperature, and the drying temperature and time are 80° C. and 1 h respectively.
[0026] In the step (2), the mass ratio of fluorinated graphene, 3-(trimethylsilyl)phenylboric acid and palladium catalyst is 5:2:0.1, the ratio of fluorinated graphene to distilled water is 2g:30mL, the heating temperature and time are 80°C and 30min respectively, and the drying temperature and time are 80°C and 30min respectively.
[0027] The preparation method of the palladium catalyst in the step (2) is as follows: an aluminum nitrate solution is mixed with silicon dioxide to form a mixed solution, the pH of the mixed solution is adjusted to 6, and then a solid is obtained by calcination, and the solid is put into a sodium chloropalladate solution, and the solid is dried and calcined to obtain a palladium catalyst. The mass ratio of the aluminum nitrate solution to the silicon dioxide is 2:1.8, wherein the mass fraction of the aluminum nitrate solution is 10%, the calcination temperature is 200°C, and the mass ratio of the solid to the sodium chloropalladate solution is 1:0.15, wherein the mass fraction of the sodium chloropalladate solution is 20%.
[0028] The fluorine-containing elastomer polymer is composed of polytrifluoropropylmethylsiloxane and polyvinylidene fluoride-hexafluoropropylene copolymer in a mass ratio of 1:1, the organic acid is acetic acid, the solvent is acetone, and the vulcanizing agent is composed of trithiocyanate monosodium salt and hydroquinone in a mass ratio of 1:1.
[0029] The preparation method of the super hydrophobic thermal conductive insulating coating is as follows: adding the modified graphene into a solvent, stirring and dispersing the mixture, and then adding other raw material components, stirring and mixing the mixture, so as to obtain the super hydrophobic thermal conductive insulating coating.
[0030] The silica was purchased from: Jikang / 631-86-9, polytrifluoropropylmethylsiloxane was purchased from: Shineng / 63148-56-1, polyvinylidene fluoride-hexafluoropropylene copolymer was purchased from: Lanabai / 9011-17-0, and sodium thiocyanate was purchased from: Jiahui Xingcheng / 41450-97-9.
[0031] A super hydrophobic thermally conductive insulating coating comprises the following raw materials in parts by weight: 90 parts of a fluorine-containing elastomer polymer, 3.5 parts of an organic acid, 350 parts of a solvent, 3.5 parts of a vulcanizing agent and 30 parts of modified graphene. The modified graphene is prepared by fluorinating graphene oxide to obtain fluorinated graphene, and then introducing a hydrophobic group to obtain the modified graphene.
[0032] The preparation method of the modified graphene comprises the following steps:
[0033] (1) ultrasonically mixing graphene oxide with distilled water, then adding ammonium fluorotitanate and boric acid and stirring and mixing, and transferring to a reactor for heating, and then cooling and washing with distilled water, and drying in a drying oven to obtain fluorinated graphene;
[0034] (2) fluorinated graphene, 3-(trimethylsilyl)phenylboronic acid and distilled water are mixed, and then a palladium catalyst is added and heated. After cooling, the mixture is washed with distilled water and dried to obtain modified graphene.
[0035] In the step (1), the ratio of graphene oxide, distilled water, ammonium fluorotitanate and boric acid is 110 mg:110 mL:1.5 g:1 g, wherein the graphene oxide is composed of nano-graphene oxide and micro-graphene oxide in a mass ratio of 1:1, and the stirring and mixing time is 7 minutes.
[0036] The heating temperature and time in step (1) are 170° C. and 5.5 h respectively, the cooling refers to cooling to room temperature, and the drying temperature and time are 90° C. and 1.5 h respectively.
[0037] In the step (2), the mass ratio of fluorinated graphene, 3-(trimethylsilyl)phenylboric acid and palladium catalyst is 7:2:0.15, the ratio of fluorinated graphene to distilled water is 2g:35mL, the heating temperature and time are 100°C and 45min respectively, and the drying temperature and time are 90°C and 30min respectively.
[0038] The preparation method of the palladium catalyst in the step (2) is as follows: an aluminum nitrate solution is mixed with silicon dioxide to form a mixed solution, the pH of the mixed solution is adjusted to 6, and then a solid is obtained by calcination, and the solid is put into a sodium chloropalladate solution, and the solid is dried and calcined to obtain a palladium catalyst. The mass ratio of the aluminum nitrate solution to the silicon dioxide is 2:1.8, wherein the mass fraction of the aluminum nitrate solution is 15%, the calcination temperature is 250°C, and the mass ratio of the solid to the sodium chloropalladate solution is 1:0.16, wherein the mass fraction of the sodium chloropalladate solution is 28%.
[0039] The fluorine-containing elastomer polymer is composed of polytrifluoropropylmethylsiloxane and polyvinylidene fluoride-hexafluoropropylene copolymer in a mass ratio of 1:1, the organic acid is acetic acid, the solvent is acetone, and the vulcanizing agent is composed of trithiocyanate monosodium salt and hydroquinone in a mass ratio of 1:1.
[0040] The preparation method of the super hydrophobic thermal conductive insulating coating is as follows: adding the modified graphene into a solvent, stirring and dispersing the mixture, and then adding other raw material components, stirring and mixing the mixture, so as to obtain the super hydrophobic thermal conductive insulating coating.
[0041] The silica was purchased from: Jikang / 631-86-9, polytrifluoropropylmethylsiloxane was purchased from: Shineng / 63148-56-1, polyvinylidene fluoride-hexafluoropropylene copolymer was purchased from: Lanabai / 9011-17-0, and sodium thiocyanate was purchased from: Jiahui Xingcheng / 41450-97-9.
[0042] A super hydrophobic thermally conductive insulating coating comprises the following raw materials in parts by weight: 100 parts of a fluorine-containing elastomer polymer, 5 parts of an organic acid, 400 parts of a solvent, 5 parts of a vulcanizing agent and 40 parts of modified graphene. The modified graphene is prepared by fluorinating graphene oxide to obtain fluorinated graphene, and then introducing a hydrophobic group to obtain the modified graphene.
[0043] The preparation method of the modified graphene comprises the following steps:
[0044] (1) ultrasonically mixing graphene oxide with distilled water, then adding ammonium fluorotitanate and boric acid and stirring and mixing, and transferring to a reactor for heating, and then cooling and washing with distilled water, and drying in a drying oven to obtain fluorinated graphene;
[0045] (2) fluorinated graphene, 3-(trimethylsilyl)phenylboronic acid and distilled water are mixed, and then a palladium catalyst is added and heated. After cooling, the mixture is washed with distilled water and dried to obtain modified graphene.
[0046] In the step (1), the ratio of graphene oxide, distilled water, ammonium fluorotitanate and boric acid is 120 mg:120 mL:2 g:1 g, wherein the graphene oxide is composed of nano-graphene oxide and micro-graphene oxide in a mass ratio of 1:1, and the stirring and mixing time is 9 minutes.
[0047] The heating temperature and time in step (1) are 180° C. and 6 h respectively, the cooling refers to cooling to room temperature, and the drying temperature and time are 100° C. and 2 h respectively.
[0048] In the step (2), the mass ratio of fluorinated graphene, 3-(trimethylsilyl)phenylboric acid and palladium catalyst is 8:2:0.2, the ratio of fluorinated graphene to distilled water is 2g:40mL, the heating temperature and time are 120°C and 60min respectively, and the drying temperature and time are 100°C and 30min respectively.
[0049] The preparation method of the palladium catalyst in the step (2) is as follows: an aluminum nitrate solution is mixed with silicon dioxide to form a mixed solution, the pH of the mixed solution is adjusted to 6, and then a solid is obtained by calcination, and the solid is put into a sodium chloropalladate solution, and the solid is dried and calcined to obtain a palladium catalyst. The mass ratio of the aluminum nitrate solution to the silicon dioxide is 2:1.8, wherein the mass fraction of the aluminum nitrate solution is 20%, the calcination temperature is 300°C, and the mass ratio of the solid to the sodium chloropalladate solution is 1:0.18, wherein the mass fraction of the sodium chloropalladate solution is 35%.
[0050] The fluorine-containing elastomer polymer is composed of polytrifluoropropylmethylsiloxane and polyvinylidene fluoride-hexafluoropropylene copolymer in a mass ratio of 1:1, the organic acid is acetic acid, the solvent is acetone, and the vulcanizing agent is composed of trithiocyanate monosodium salt and hydroquinone in a mass ratio of 1:1.
[0051] The preparation method of the super hydrophobic thermal conductive insulating coating is as follows: adding the modified graphene into a solvent, stirring and dispersing the mixture, and then adding other raw material components, stirring and mixing the mixture, so as to obtain the super hydrophobic thermal conductive insulating coating.
[0052] The silica was purchased from: Jikang / 631-86-9, polytrifluoropropylmethylsiloxane was purchased from: Shineng / 63148-56-1, polyvinylidene fluoride-hexafluoropropylene copolymer was purchased from: Lanabai / 9011-17-0, and sodium thiocyanate was purchased from: Jiahui Xingcheng / 41450-97-9.
[0053] Comparative Example 1
[0054] On the basis of Example 2, a super hydrophobic thermally conductive insulating coating is provided, which comprises the following raw materials in parts by weight: 90 parts of fluorine-containing elastomer polymer, 3.5 parts of organic acid, 350 parts of solvent, 3.5 parts of vulcanizing agent and 30 parts of graphene.
[0055] The fluorine-containing elastomer polymer is composed of polytrifluoropropylmethylsiloxane and polyvinylidene fluoride-hexafluoropropylene copolymer in a mass ratio of 1:1, the organic acid is acetic acid, the solvent is acetone, and the vulcanizing agent is composed of trithiocyanate monosodium salt and hydroquinone in a mass ratio of 1:1.
[0056] The preparation method of the super hydrophobic thermal conductive insulating coating is as follows: adding the modified graphene into a solvent, stirring and dispersing the mixture, and then adding other raw material components, stirring and mixing the mixture, so as to obtain the super hydrophobic thermal conductive insulating coating.
[0057] The polytrifluoropropylmethylsiloxane was purchased from: Shineng / 63148-56-1, the polyvinylidene fluoride-hexafluoropropylene copolymer was purchased from: Lanabai / 9011-17-0, and the monosodium thiocyanate was purchased from: Jiahui Xingcheng / 41450-97-9.
[0058] Comparative Example 2
[0059] On the basis of Example 2, a super hydrophobic thermally conductive insulating coating is provided, which comprises the following raw materials in parts by weight: 90 parts of fluorine-containing elastomer polymer, 3.5 parts of organic acid, 350 parts of solvent, 3.5 parts of vulcanizing agent and 30 parts of fluorinated graphene.
[0060] The preparation method of the fluorinated graphene comprises the following steps:
[0061] (1) Graphene oxide is ultrasonically mixed with distilled water, and then ammonium fluorotitanate and boric acid are added and stirred, and then transferred into a reactor for heating, and then cooled and washed with distilled water, and then placed in a drying oven for drying to obtain fluorinated graphene.
[0062] In the step (1), the ratio of graphene oxide, distilled water, ammonium fluorotitanate and boric acid is 110 mg:110 mL:1.5 g:1 g, wherein the graphene oxide is composed of nano-graphene oxide and micro-graphene oxide in a mass ratio of 1:1, and the stirring and mixing time is 7 minutes.
[0063] The heating temperature and time in step (1) are 170° C. and 5.5 h respectively, the cooling refers to cooling to room temperature, and the drying temperature and time are 90° C. and 1.5 h respectively.
[0064] The fluorine-containing elastomer polymer is composed of polytrifluoropropylmethylsiloxane and polyvinylidene fluoride-hexafluoropropylene copolymer in a mass ratio of 1:1, the organic acid is acetic acid, the solvent is acetone, and the vulcanizing agent is composed of trithiocyanate monosodium salt and hydroquinone in a mass ratio of 1:1.
[0065] The preparation method of the super hydrophobic thermal conductive insulating coating is as follows: adding the modified graphene into a solvent, stirring and dispersing the mixture, and then adding other raw material components, stirring and mixing the mixture, so as to obtain the super hydrophobic thermal conductive insulating coating.
[0066] The polytrifluoropropylmethylsiloxane was purchased from: Shineng / 63148-56-1, the polyvinylidene fluoride-hexafluoropropylene copolymer was purchased from: Lanabai / 9011-17-0, and the monosodium thiocyanate was purchased from: Jiahui Xingcheng / 41450-97-9.
[0067] Comparative Example 3
[0068] On the basis of Example 2, the monosodium thiocyanate in the vulcanizing agent was removed and replaced with an equal mass of hydroquinone, and the other conditions were the same as those in Example 2.
[0069] Comparative Example 4
[0070] On the basis of Example 2, hydroquinone in the vulcanizing agent was removed and replaced with an equal mass of monosodium thiocyanate; other conditions were the same as those in Example 2.
[0071] 1. Performance Testing
[0072] Thermal conductivity test and insulation test: The coatings prepared in Example 2 and Comparative Examples 1-2 were coated with the same thickness on both sides of 1030 aluminum foil plates of the same specifications and used as samples. The thermal conductivity of the samples was measured by a DZDR-S thermal conductivity meter, and the samples were tested for volume resistivity using a 7122 AC / DC withstand voltage insulation tester. The volume resistance module of the instrument was used to measure the volume resistance of the samples and calculate the volume resistivity of the coating. The specific formula is: , where P v is the volume resistivity, R v is the volume resistance, s is the effective area of the electrode, and h is the thickness of the sample;
[0073] Determination of hydrophobicity: The coatings prepared in Example 2 and Comparative Examples 1-2 were used as samples, and the coatings of the same thickness were coated on aluminum foil plates of the same specifications, and the contact angle (CA) and the rolling angle (SA) were measured using a contact angle meter. The coating contact angle was the average of the contact angles measured at three different points on the surface of the sample using a 4 μL water droplet, and the rolling angle was the average of the rolling angles measured at three different points on the surface of the sample using a 10 μL water droplet;
[0074] Surface drying time test: The coatings prepared in Example 2 and Comparative Examples 3-4 were used as samples, coated on aluminum foil plates at the same thickness at room temperature, and the surface drying time was measured using the cotton ball blowing method.
[0075] The above test results are shown in Table 1.
[0076] Table 1 Test results
[0077]
[0078] Note: Critical resistivity of insulating materials (10 7 Ω·m)
[0079] From Table 1, it can be concluded that the volume resistivity of Example 2 is 0.76, which is 0.04 different from Comparative Example 1, and is close to Comparative Example 2. The volume resistivity of Example 2 is greater than the critical resistivity of the insulating material, while that of Comparative Example 1 is much less than 10. 7 Ω·m, comparative example 2 is equal to 10 7 Ω·m, the contact angle of Example 2 is the largest and greater than 150°, and the rolling angle is the smallest and less than 10°. Therefore, Example 2 has good thermal conductivity, insulation and super hydrophobic effect; Comparative Example 1 uses graphene as a filler, which has excellent conductivity and does not achieve super hydrophobic effect; Comparative Example 2 uses fluorinated graphene as a filler, and its volume resistivity is less than that of Example 2, and its insulation effect is worse than that of Example 2. Since Comparative Example 2 does not use 3-(trimethylsilyl)phenylboronic acid to further modify the fluorinated graphene, its dispersibility and compatibility with the fluorinated elastomer polymer are poor, so the super hydrophobic effect is worse than that of Example 2; Comparative Examples 3-4 add a single vulcanizing agent, which affects the speed of film formation. When monosodium thiocyanate and hydroquinone act together, the film formation process is both rapid and stable.
[0080] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A super hydrophobic thermally conductive insulating coating, characterized in that: The super hydrophobic thermal conductive insulating coating comprises the following raw materials in parts by weight: 80-100 parts of fluorine-containing elastomer polymer, 2-5 parts of organic acid, 300-400 parts of solvent, 2-5 parts of vulcanizing agent and 20-40 parts of modified graphene. The preparation method of the modified graphene is: firstly fluorinating graphene oxide to obtain fluorinated graphene, and then introducing hydrophobic groups to obtain modified graphene; The preparation method of the modified graphene comprises the following steps: (1) ultrasonically mixing graphene oxide with distilled water, then adding ammonium fluorotitanate and boric acid and stirring and mixing, and transferring to a reactor for heating, and then cooling and washing with distilled water, and drying in a drying oven to obtain fluorinated graphene; (2) mixing fluorinated graphene, 3-(trimethylsilyl)phenylboronic acid and distilled water, then adding a palladium catalyst and heating, cooling and washing with distilled water, and drying to obtain modified graphene; In the step (1), the ratio of graphene oxide, distilled water, ammonium fluorotitanate and boric acid is 100-120 mg: 100-120 mL: 1-2 g: 1 g, wherein the graphene oxide is composed of nano-graphene oxide and micro-graphene oxide in a mass ratio of 1:1, and the stirring and mixing time is 6-9 min; In the step (2), the mass ratio of the fluorinated graphene, 3-(trimethylsilyl)phenylboric acid and palladium catalyst is 5-8:2:0.1-0.2, the ratio of the fluorinated graphene to distilled water is 2 g:30-40 mL, the heating temperature and time are 80-120° C. and 30-60 min, respectively, and the drying temperature and time are 80-100° C. and 30 min, respectively; The fluorine-containing elastomer polymer is composed of polytrifluoropropylmethylsiloxane and polyvinylidene fluoride-hexafluoropropylene copolymer in a mass ratio of 1:1, the organic acid is acetic acid, the solvent is acetone, and the vulcanizing agent is composed of trithiocyanate monosodium salt and hydroquinone in a mass ratio of 1:
1.
2. The super hydrophobic thermally conductive insulating coating according to claim 1, characterized in that: The heating temperature and time in step (1) are 160-180° C. and 5-6 h respectively, the cooling refers to cooling to room temperature, and the drying temperature and time are 80-100° C. and 1-2 h respectively.
3. The super hydrophobic thermally conductive insulating coating according to claim 1, characterized in that: The preparation method of the palladium catalyst in the step (2) is as follows: an aluminum nitrate solution is mixed with silicon dioxide to form a mixed solution, the pH of the mixed solution is adjusted to 6, and then a solid is obtained by calcination, and the solid is placed in a sodium chloropalladate solution, and the palladium catalyst is obtained after drying and calcination. The mass ratio of the aluminum nitrate solution to the silicon dioxide is 2:1.8, wherein the mass fraction of the aluminum nitrate solution is 10-20%, the calcination temperature is 200-300°C, and the mass ratio of the solid to the sodium chloropalladate solution is 1:0.15-0.18, wherein the mass fraction of the sodium chloropalladate solution is 20-35%.
4. The super hydrophobic thermally conductive insulating coating according to claim 1, characterized in that: The preparation method of the super hydrophobic thermal conductive insulating coating is as follows: adding the modified graphene into a solvent, stirring and dispersing the mixture, and then adding other raw material components, stirring and mixing the mixture, so as to obtain the super hydrophobic thermal conductive insulating coating.
Citation Information
Patent Citations
Fluorinated graphene modified fluororesin coating and preparation method thereof
CN112375449A
Preparation method of graphene modified anticorrosive paint
CN118146697A